Bertrand and Cournot oligopolies when rivals' costs are unknown - Ferreira, Fernanda A. (2014)
We study Bertrand and Cournot oligopoly models with incomplete information about rivals’ costs, where the uncertainty is given by a uniform distribution. We compute the Bayesian- Nash equilibrium of both games, the ex-ante expected proﬁts and the ex-post proﬁts of each ﬁrm. We see that, in the price competition, even though only one ﬁrm produces in equilibrium, all ﬁrms have a positive ex-ante expected proﬁt.